(untitled) (Nativa, 2023)
ABSTRACT: Cowpea has great socioeconomic importance for the Northeast region of Brazil. However, this region suffers from water scarcity, leading to reduced production. Therefore, it is important to identify varieties adapted to water stress conditions. With that aim, this work characterized cowpea creole varieties at the seedling stage using ISSR markers and the Screening Box method. DNA samples extracted from 50 creole varieties were evaluated using ISSR markers. Among them, two were used as controls, one tolerant (Pingo de Puro 1,2) and the other susceptible (Santo Inácio) to drought. Multivariate and cluster analyses were used to identify genetic variability for drought tolerance. Then, an experiment using the Screening Box method was carried out under a greenhouse, where water deficit was induced in 22 varieties, including the control ones. These plants were selected based on the genetic characterization performed with the ISSR. In the first experiment, 45 varieties were grouped with the control creole varieties. Some showed a small genetic distance from the tolerant, indicating genetic similarity. However, significant differences were observed among creole varieties in the greenhouse experiment. In conclusion, nine landraces can be considered tolerant to water stress according to the results of the experiments. Keywords: ISSR markers; genetic characterization; DNA. Tolerância ao estresse hídrico em diferentes variedades de feijão-caupi em fase de plântula RESUMO: O feijão-caupi tem grande importância socioeconômica para a região Nordeste do Brasil. No entanto, esta região sofre com a escassez de água, levando à redução da produção. Portanto, é importante identificar variedades adaptadas às condições de estresse hídrico. Objetivou-se caracterizar variedades crioulas de feijão-caupi na fase de muda, utilizando marcadores ISSR e o método Screening Box. Utilizando marcadores ISSR, foram avaliadas amostras de DNA extraídas de 50 variedades. Dentre elas, duas foram utilizadas como testemunhas, uma tolerante (Pingo de Puro 1,2) e outra suscetível (Santo Inácio) à seca. Para identificar a variabilidade genética para tolerância à seca, foram utilizadas análises multivariadas e de agrupamento. Em seguida, foi realizado um experimento utilizando o método Screening Box, onde foi induzido déficit hídrico em 22 variedades, incluindo as testemunhas. Essas plantas foram selecionadas com base na caracterização genética realizada com o ISSR. No primeiro experimento, 45 variedades foram agrupadas com as variedades crioulas de controle. Alguns deles apresentaram uma pequena distância genética dos tolerantes, o que indica similaridade genética. No entanto, no experimento em casa de vegetação, foram observadas diferenças significativas entre as variedades crioulas. Concluindo, nove variedades crioulas podem ser consideradas tolerantes ao estresse hídrico de acordo com os resultados dos experimentos. Palavras-chave: marcadores ISSR; caracterização genética; DNA.